INNOVATIVE TOPICAL THERAPIES FOR RADIATION-INDUCED SKIN INJURIES IN BREAST CANCER PATIENTS: A COMPARATIVE CLINICAL STUDY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Radiation therapy remains a cornerstone in the management of breast cancer; however, radiation-induced skin injuries (radiodermatitis) significantly affect patients’ quality of life and may interrupt treatment schedules. Despite advances in radiotherapy techniques, acute and chronic cutaneous toxicities remain prevalent. The present study evaluates the clinical effectiveness of innovative topical therapeutic agents, including hyaluronic acid-based formulations, corticosteroid creams, and herbal bioactive compounds, in the prevention and management of radiation-induced skin damage in breast cancer patients.
Keywords: Radiodermatitis; Breast cancer; Radiation therapy; Topical treatment; Hyaluronic acid; Skin toxicity; Oncology supportive care.